Paving the way for coastal resources management the Bolinao experience (1993-97). - McManus, L. T.; Menez, M. A. J.; Alino, E. M.; Ferrer, E. M.; Dizon, J. C. A. (eds.) (2001)
A terminal report of the Project Community-Based Coastal Resources Management (CBCRM) Centre File: 94-0021/40156